Potensi Pajak Restoran di Kabupaten Sleman - Widyatmoyo, Widyatmoyo; Pramudyo, Anung (208-7721)
This research aims to know the potential Tax Restaurant in Sleman Regency. This research was conducted at the Office of Sleman Regency Area Income. The method used is descriptive statistics using a quantitative method for analyzing the growth, the rate of collection, status of performance and its contribution to the income of the original area (PAD). The projection is used to calculate the potential for some period to come and see a comparison of the influence of PERDA No. 2 in 2011. In addition the study also utilize primary data to find out the potential taxpayer Restaurant in the bustling locations based on the standards and campus in Sleman Regency.The research results show that the value of the tax restaurant from 2008 up to 2013 has been steadily rise. Restaurant tax from 2008 up to 2013 having the average contribution against taxes of regional 10.1 percent and the average contribution to pad as much as 5.3 percent. By the enactment of bylaw no. 2 in 2011 on restaurant tax which will come into effect starting in 2012 thought to have potential revenue increase tax as much as 16.8 percent compared to using the regulations before. The potential of the restaurant tax sleman district 2014 is estimated at IDR 22.776.189.184,79 beyond a target that has been determined that is IDR 17.500.000.000. While the potential of the restaurant tax sleman district 2015 estimated IDR 25.384.968.521.86. An analysis of the potential of the side of the number of taxpayers who can still dug based on survey the number of taxpayers in the field based on the base of the road is still could be improved until 139 percent, with a note to the region with the busy street. The potential for more on the site around campus as the center of which reached 538,31 percent.